Regeneration of Frost-liable Forests in the Central Provinces - Sagreiya, K. P. (Indian Forester, 1937)
On the presumption that frest-bite in plants is caused when temperature of the surrounding cold air falls below a certain level, the writer suggests a method of preventing frost by inducing circulation of the stagnant cold air by cutting a series of strips across the frost-liable depression running in the direction of the prevailing wind in the locality.